Leveraging Community Partnerships to Engage Digitally Foreign Learners in Response to COVID-19 - W. Keith Burgess; Jimmeka L Anderson (Middle Grades Review, 2020)
This practitioner perspective discusses how creating and leveraging community partnerships in response to COVID-19 enhanced remote learning with science curriculum in an urban middle school with digitally foreign learners. The term digitally foreign learners was coined by the authors to contextualize the experiences of students with limited digital learning both at home and in school as a result of the digital divide. By developing a partnership with the nonprofit organization, I AM not the MEdia, Inc., along with parents and an external educator, the authors describe how a classroom blog site was created that enhanced remote learning engagement with students and families in a high poverty community. Strategies for addressing technology inequities and engaging digitally foreign learners through digital curriculum is provided.
Keywords: digitally foreign learners; urban schools; middle grades; remote learning